2013
DOI: 10.1115/1.4023866
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Localized Modes of Harmonic Oscillations in Nonlinear Oscillator Arrays

Abstract: Intrinsic localized modes (ILMs) are investigated in an array with N Duffing oscillators that are weakly coupled with each other when each oscillator is subjected to sinusoidal excitation. The purpose of this study is to investigate the behavior of ILMs in nonlinear multi-degree-of-freedom (MDOF) systems. In the theoretical analysis, van der Pol's method is employed to determine the expressions for the frequency response curves for fundamental harmonic oscillations. In the numerical calculations, the frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…In the free case, a nonlinear modal analysis is carried out, and we demonstrate that localised states bifurcate from the homogeneous out-of-phase mode. The results are similar to bifurcated states calculated in smooth systems, such as in chains of Duffing oscillators [12,15,19]. In the case of externally driven vibration, if the excitation is perfectly in phase, three kinds of stable response states may result.…”
Section: Introductionsupporting
confidence: 81%
“…In the free case, a nonlinear modal analysis is carried out, and we demonstrate that localised states bifurcate from the homogeneous out-of-phase mode. The results are similar to bifurcated states calculated in smooth systems, such as in chains of Duffing oscillators [12,15,19]. In the case of externally driven vibration, if the excitation is perfectly in phase, three kinds of stable response states may result.…”
Section: Introductionsupporting
confidence: 81%
“…The frequency response was obtained by solving the derived equation of motion using Van Der Pols method. The authors showed the effect of the linear coupling spring an added imperfection on the soliton and they proved these results on an array of Duffing oscillators [9] subject to an external excitation.…”
Section: Introductionmentioning
confidence: 80%
“…Herein, we particularly focus on nonlinear localization [8] of the mutual bubble interaction in which the total vibrational energy of the system is confined to some bubbles due to the nonlinearity of the bubble oscillation even though they are equally-sized and arranged in a symmetric configuration. This symmetry breaking property is one of the distinctive feature of the localized oscillation [14,15] considered in this study. This symmetrical arrangements and equal-sized assumption have been used in numerical investigation of the effects of bubble sizes and spatial arrangement on the coupled bubble dynamics [11,12,13,16].…”
Section: Introductionmentioning
confidence: 79%